Akuntabilitas Insentif Guru Paud Berbasis Bukti: Pengembangan Sistem Pelaporan Melalui Participatory Action Research - Bayu Saputra Dullah; Syahrial Labaso; Ratna Hestiana; Ulfa Dj. Nurkamiden (Sevaka : Hasil Kegiatan Layanan Masyarakat, 2026)
Village-funded incentives for early childhood education teachers are often accounted for only through attendance records, leaving teachers' pedagogical contributions insufficiently documented. This study developed and assessed the initial feasibility of an evidence-based performance reporting system through Participatory Action Research in three early childhood education centers in Luhu Village, Gorontalo Regency. Five incentive-recipient teachers, three center heads, five village government representatives, and an academic team participated in cycles of diagnosis, co-design, action, observation, and reflection. The final system required four minimum forms of evidence: attendance records, activity photographs compliant with child-privacy protocols, teaching modules, and children's worksheets or portfolios. Document completeness for photographs, modules, and portfolios increased from 15%, 20%, and 5% to 95%, 90%, and 85%, respectively. The mean Accountability Evidence Index increased from 31.24 to 86.76. All teachers improved, although the two-sided Wilcoxon test did not reach the 0.05 threshold because of the very small sample (W = 0; p = 0.063). Inter-rater agreement was substantial (kappa = 0.74). Feasibility depended on simple indicators, clear verification roles, manageable documentation, and child-data protection.